Pre-weaning kid and lamb losses in traditional African management systems - Wilson, R.T.; Traoré, A.; Peacock, C.P.; Mack, S.D.; Agyemang, K. (International Livestock Centre for Africa, 1985)
Discusses pre-weaning mortality in kids, ages at death and causes of death in the traditionally managed African small ruminant farms. Presents data on pre-weaning death rates of lambs for different variables (system, sex, birth type, birth season, parity & flock) at six sites (Sudan, Mali, Kenya, Nigeria & Ethiopia).